2018
DOI: 10.1016/j.srhc.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian obstetricians’ experiences of the use of ultrasound in pregnancy management. A qualitative study

Abstract: This study highlights obstetricians' experiences and views of ultrasound and prenatal diagnosis in Norwegian maternity care and the challenges associated with the provision of these services, including counselling dilemmas and perceived differences in expectations between caregivers and expectant parents. There was notable diversity among these obstetricians in relation to their support of, and adherence to Norwegian regulations about the use of ultrasound, which indicates that the care pregnant women receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…The findings of the CROCUS study in Rwanda also demonstrated that health professionals not themselves performing ultrasounds have more liberal attitudes towards ultrasound use than health professionals performing these examinations 29. Health professionals sometimes fear that ‘routinisation’ of ultrasound as an unquestioned and integral part of pregnancy management can exert a negative impact on pregnant women’s informed consent, and that its increasing use for fetal examination may have consequences for how disability is viewed in society 25 26 30. The use of ultrasound may also reduce attention on important clinical parameters such as measurement of blood pressure and proteinuria 7 24.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the CROCUS study in Rwanda also demonstrated that health professionals not themselves performing ultrasounds have more liberal attitudes towards ultrasound use than health professionals performing these examinations 29. Health professionals sometimes fear that ‘routinisation’ of ultrasound as an unquestioned and integral part of pregnancy management can exert a negative impact on pregnant women’s informed consent, and that its increasing use for fetal examination may have consequences for how disability is viewed in society 25 26 30. The use of ultrasound may also reduce attention on important clinical parameters such as measurement of blood pressure and proteinuria 7 24.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous qualitative research within the CROss Country Ultrasound Study (CROCUS) in Norway has demonstrated that Norwegian obstetricians experience challenges associated with provision of ultrasound and prenatal diagnosis services, including counselling dilemmas and perceived differences in expectations between caregivers and expectant parents [16]. From our quantitative CROCUS Study in Norway we have reported midwives’ and obstetricians’ views on how many ultrasound examinations should be part of standard care during pregnancy [17].…”
Section: Introductionmentioning
confidence: 99%
“…Obstetricians sensed parents' misperceptions regarding scans 26 and explained this by highlighting that ultrasound is frequently used when complications are not expected 28 . This lack of understanding in parents made the task of communicating news harder for staff 26,28 …”
Section: Resultsmentioning
confidence: 99%
“…Studies in HCPs found that delivering unexpected news was challenging for HCPs 26,30 . Some said it carried a high emotional toll; they both feared these events occurring and then ruminated on them once they had passed 26,30 . Some HCPs drew on the positive aspects of their work and collegial support to cope 30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation